FASIES KARBONAT FORMASI CAMPURDARAT DI DAERAH TULUNGAGUNG, JAWA TIMUR - Praptisih, Praptisih; Siregar, M. Safei (Jurnal Geologi dan Sumberdaya Mineral, 2012)
The Campurdarat Formation is one of the carbonate rocks exposed in the Tulungagung areas and its surrounding, East Java. Detail investigation for studying facies and sedimentation of this limestone has been conducted. The investigation include field investigation and laboratory method, consisting of petrography and micropaleontology. The result of petrographic analysis showed that the carbonate rocks in the area investigation can be divided into four types of facies such as packstone, floatstone, rudstone and boundstone. Packstone facies was deposited from the backreef – lagoon environment, floatstone facies in backreef and coral zones environments, rudstone facies in the reef zone environment and boundstone facies formed starting from the reef front - reef crest. The Campurdarat carbonate rocks are interpreted to represent a barrier – reef of Early Miocene age.Key words : Campurdarat Formation , facies, carbonate, environment, sedimentation, reef, Tulungagung